New Design of A Micro-Hydro Power Plant (MHPP) System In The 3T Region As Al-ternative Solution Unit Turbine Using Computational Fluid Dynamics (CFD) Simulation - Syed Jarrar Pirzada; Intan Kurniawan; Nidia Pialina Nababan; ⁠Taufik Roni Sahroni (Green Publisher Indonesia, 2024)
This research aims to select the most suitable type of water turbine for the micro-hydro power plant (PLTMH) site in the Anggi District, Pegunungan Arfak Regency, West Papua Province. The study also aims to design the most optimal and effective turbine in terms of technical aspects and generator system reliability. This objective is directed towards providing recommendations for the development of the second unit of PLTMH Anggi in a more comprehensive manner rather than relying solely on expert recommendations without thorough analysis. The data used in this research was obtained from field surveys and secondary data sources. The initial step in selecting the turbine type involves manual turbine design calculations, taking into consideration parameters such as water flow, head height, and hydraulic efficiency. Based on these calculation results, the